2013
DOI: 10.1016/j.cell.2013.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Tumor Oncogenes by Disruption of Super-Enhancers

Abstract: Summary Chromatin regulators have become attractive targets for cancer therapy, but it is unclear why inhibition of these ubiquitous regulators should have gene-specific effects in tumor cells. Here, we investigate how inhibition of the widely expressed transcriptional coactivator BRD4 leads to selective inhibition of the MYC oncogene in multiple myeloma (MM). BRD4 and Mediator were found to co-occupy thousands of enhancers associated with active genes. They also co-occupied a small set of exceptionally large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

114
3,107
3
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,518 publications
(3,228 citation statements)
references
References 85 publications
114
3,107
3
4
Order By: Relevance
“…Under this condition, BRD2 binding was almost completely depleted at a global level (Figure 4(a)). Consistent with previous studies[6,16], we did not observe any global changes in H3K27ac level (Fig. S7A).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Under this condition, BRD2 binding was almost completely depleted at a global level (Figure 4(a)). Consistent with previous studies[6,16], we did not observe any global changes in H3K27ac level (Fig. S7A).…”
Section: Resultssupporting
confidence: 93%
“…In a complementary analysis, we examined the enrichment of bromodomain proteins BRD2, BRD4, and EP300 at the H4K5acK8ac sites using the publicly available ChIP-seq datasets from the closely related cell types: BRD4 ChIP-seq from SCLC cell line H2171 (GSM1038270) [16] and ENCODE P300 ChIP-seq from NSCLC A549 [25]. We found that promoter- and enhancer-associated H4K5acK8ac regions were enriched for BRD2, BRD4, and EP300 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4). Consistent with prior literature, super enhancer (SE) domains were significantly associated with greater transcriptional load 69 (Extended Data Fig. 4).…”
supporting
confidence: 89%